1979
DOI: 10.1073/pnas.76.2.722
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-dependent ATPase activity of bovine heart protein kinase.

Abstract: The adenosine 3',5'-monophosphate (cAMP) dependent ATPase (ATP phosphohydrolase, EC 3.6.1.3) activity of cAMP-dependent protein kinase (ATP:protein phosphotransferase, EC 2.7.1.37) from bovine heart is characterized. That the ATPase activity is intimately associated with the catalytic subunit of the enzyme is suggested by the following: (i) the similar dependences of ATPase and protein kinase activities on cAMP; (ii) the dissociation of ATPase activity from the holoenzyme on addition of cAMP and its co-elution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 10 publications
5
30
0
Order By: Relevance
“…4B), as expected based on the crystal structure of PKR (Dar et al 2005). This K d is similar to that seen for ATP binding to other kinases such as PKA and MAPK (Armstrong et al 1979;Setyawan et al 1999), and in agreement with a value from Cole and coworkers of 20 6 2 mM, measured for ATP binding to K296R using competition fluorescence anisotropy experiments (Lemaire et al 2006). The second site was tighter in affinity (K d = 3.9 6 1.4 mM) but with a small binding stoichiometry of n = 0.11 6 0.09 (Fig.…”
Section: Recognition Of Atp Has Specificity For the Nucleobase: Itc Esupporting
confidence: 73%
“…4B), as expected based on the crystal structure of PKR (Dar et al 2005). This K d is similar to that seen for ATP binding to other kinases such as PKA and MAPK (Armstrong et al 1979;Setyawan et al 1999), and in agreement with a value from Cole and coworkers of 20 6 2 mM, measured for ATP binding to K296R using competition fluorescence anisotropy experiments (Lemaire et al 2006). The second site was tighter in affinity (K d = 3.9 6 1.4 mM) but with a small binding stoichiometry of n = 0.11 6 0.09 (Fig.…”
Section: Recognition Of Atp Has Specificity For the Nucleobase: Itc Esupporting
confidence: 73%
“…Reactions performed by combining a drop containing PKA and ATP with a drop containing Kemptide and ATP did not yield information on the K M of ATP (not shown). It is important to note that product inhibition by ADP ( K I = 7.3 μM; [23]) might a factor because the enzyme concentration used here in the initial drop (4 μM) was high enough that the intrinsic ATPase activity of PKA catalytic subunit (0.74 min −1 ; [25]) produced significant ADP in the time between mixing the enzyme with ATP and the addition of the Kemptide.…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach was used to define the metal-binding sites in crystals of the porcine C subunit crystallized in the presence of inhibitor peptide and p[NH]ppA [7]. The metal requirements for the PKA C subunit were first described in detail by Armstrong et al [31], who showed that from two Mg 2+ -binding sites, one is required for catalysis and one is associated with inhibition. Based on crystal structures of the C subunit [7,8] and NMR studies [14] with inert complexes of ATP it was concluded that the activating metal bridges the βand γphosphates and involves an enzyme-ATP-metal bridge [14].…”
Section: Figure 5 Influence Of Metal Ion Concentration On Pka Type I mentioning
confidence: 99%